IDENTIFICATION OF THE IMPORTANCE OF UKRAINE IN INTERNATIONAL GLOBALIZATION AND INTEGRATION PROCESSES - MALCHYK, MARIANA; POPKO, OLENA; OPLACHKO, IRYNA (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The purpose of the article is to define the essence of globalization and international economic integration, to identify their influence on the development of national economies and markets, identify of Ukraine’s place in international globalization and integration processes.In this scientific research general scientific and special research methods are used, in particular, the method of theoretical generalization to clarify certain concepts such as ‘globalization’; the method of statistical analysis to assess the dynamics of the global index of globalization and the dynamics of globalization indexes of the leading countries of the world according to KOF; the method of comparative analysis for carrying out a rating assessment of the scale of Ukraine's integration into the world in terms of the economic, social and political components of globalization.Researches of the survey showed existing approaches to the interpretation of the categories ‘globalization’. It is underlined the ambiguous attitude to globalization in the scientific sphere. The rating of Ukraine according to the index of globalization of KOF, and the dynamics of the index change in 2012-2020 years are presented. Positive aspects and threats caused by the entry of Ukraine into the global space are considered.In order to increase the rating’s assessment of the scale of Ukraine’s integration into the world, it is necessary to increase the volume of international trade, to rise the level of international business activity, trade flows, flows of international investments, etc., to intensify the level of cultural integration, the level of international tourism, cross-border money transfers, information flows, etc., to ensure membership in leading international organizations, participation in international missions, processes for the ratification of international multilateral treaties, etc.
Keywords: globalization; international economic integration; globalization index; international integration processes